Increasing Students' Learning Motivation In Learning Physical Education Through Traditional Games In Elementary School (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the increase in students' learning motivation in Physical Education learning through the implementation of traditional games in elementary schools. The background of this study is based on the low learning motivation of students in participating in physical education learning, as well as the erosion of the existence of traditional games amidst the development of digital technology. The research method used is quantitative with a pre-experimental design of the one-group pretest-posttest type. The subjects of this study were 30 students in grades V and VI of SDN Nagrak. The instrument used was a learning motivation questionnaire that had been tested for validity and reliability. The results of the study showed a significant increase in students' learning motivation after being given treatment in the form of traditional games such as gobak sodor, cat-and-mouse, jump rope, hopscotch, and fortification. Based on statistical tests, a significance value of